Pengaruh Beban Kerja Terhadap Kepuasan Kerja Karyawan di PT Sinar Musi Jaya Palembang - Nisa, Khoirun; Andriana, Isni; Farla, Wita; Karimudin, Yos (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of monkey loads on employee job satisfaction at PT Sinar Musi Jaya Palembang. The population in this study are employees at PT Sinar Musi Jaya Palembang, totaling 57 people. This research uses saturation sampling technique. This study uses primary data obtained through questionnaires and analysis of simple linear regression analysis as a data analysis technique. The results of this study indicate that workload has a positive and significant effect on employee job satisfaction at PT Sinar Musi Jaya Palembang. Keywords: Workload, Job Satisfaction